EKSPLORASI POTENSI MIKROBA TANAH DALAM MENINGKATKAN HASIL PANEN KEDELAI (Glycine max) PADA LAHAN KERING - Kartina AM; Nurmayulis .; Andi Apriany Fatmawaty; Dewi Firnia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
A research has been conducted to produce products of various microbial inoculants which synergistically function as a biological fertilizer and could improve soybean production on dry land, especially land that was marginal. Excavation of potential soil microbes on marginal dry land was conducted in Cibaliung District, Pandeglang Banten with a screening technique that had been tested in comparison with isolates that had been successfully tested its superiority. After proving the superiority of microbial synergism between multiple test isolates that had different roles in the transformation of nutrients, especially N and P. Microbial isolates demonstrated synergism effect formulated with a variety of carrier as inoculant products. In this research, isolation of microbes was conducted in the first year that was isolation of Azotobacter and Azospirillum with microbial enrichment with selective liquid media Ashby and Media Okon, BPF Pikovskaya media. The selection of microbial population density, which was aimed to produce a microbial consortium to produce microbes that work synergistically enhance the growth of plants was conducted in the second year. The experiment used a randomized completely block design (RCBD ) with a population density factor Azotobacter sp., Azospirillum and BPF: without treatment ( Z0, AZ0 and BP0) , 102cfu/ml (Z1 AZ1 and BP1), 104 cfu/ml (Z2, AZ2, and BP2 ), 106 cfu/ml (Z3, AZ3 and BP3), 108 cfu/ml (Z4, AZ4 and BP4) and 1010 cfu/1ml (Z5, AZ5 and BP5) soybean plants inoculated at the age of 2 M1ST repeated four times with further testing DMRT 5%. The parameters measured were: plant height, number of leaves, root length, leaf area, dry weight and root dry weight crown. Research showed that treatment of the various levels of population density Azotobacter sp. significantly effect on plant height, while density of population Azosprillium sp. significantly effect on plant height. BPF population density showed significant effect on the number of leaves.Key words: Soybean, Azospirillum, Azotobacter, and BPF